Coronary flow assessment in unstable angina/non st-segment elevation myocardial infarction patients via thrombolysis in myocardial infarction frame count in angiography - Hamidreza Sanati; Ali Zahedmehr; Ata Firouzi; Negar Salehi; Mohsen Maadani; Farshad Shakerian; Reza Kiani; Pedram Golnari; Sepideh Parchami-Ghazaee; Mohammadmehdi Peighambari (Research in Cardiovascular Medicine, 2013)
Background: TIMI Frame Count (TFC) is one of the methods to estimate the coronary blood flow velocity. This is a simple, inexpensive, quantitative, reproducible, and continuous variable method. Many studies have been conducted on TFC assessment in ST elevation myocardial infarction (STEMI) patients. Objectives: The present study is aimed to measure the TFC in the coronary arteries of UA/NSTEMI patients to find abnormalities in diseased or patent vessels and compare with the normal values. Patients and Methods: The participants were 105 consecutive UA/NSTEMI patients who underwent coronary angiography in Shahid Rajaie Cardiovascular Medical and Research Center, Tehran, Iran in 2009. Exclusion criteria were history of CABG, PCI, or STEMI or presence of occluded arteries in angiography. We measured the coronary TFC in these patients. We examined also 55 stable patients without coronary lesions and with TIMI 3 flow to have an estimation of normal TFCs. Results: From a total of 105 patients, 25 (23.8%) had no significant coronary lesion (> 60%); 35 (33.3%) were diagnosed with single vessel disease; 22 (21%) were 2VD; and 23 (21.9%) were 3 VD.). In overall, mean TFC in UA/NSTEMI group was 28.7 (± 14) frames compared to 23.8 (± 7.8) frames in the normal group (P < 0.05). In the vessels with significant lesions, TFC was significantly higher than normal (30.84 vs. 23.8; P < 0.001) and also significantly higher than patent vessels of the same patients (30.84 vs. 26.10; P = 0.029). In these patients, patent vessels had higher TFC values compared to normal coronaries (26.10 vs. 23.8), but the difference was not significant (P = 0.12). In the patients with significant lesions, mean TFC was higher than the same value in acute coronary patients without significant lesions (29.3 vs. 27.2), but the difference was not significant (P = 0.114). In the patients who underwent PCI and stenting, TFC changed significantly after PCI toward the normal value (P = 0.001). In the patients with elevated cardiac enzymes, TFC was higher but the difference was not significant (P = 0.35). Conclusions: Patent coronaries of UA/NSTEMI patients have a trend to higher TFCs compared to normal values. Presence of significant coronary lesions in these patients significantly increases TFC.